Program Asa Cendikia Membangun Semangat Belajar Di Desa Rendang - Sulastra I Ketut Sulastra; I Wayan Numertayasa; I Komang Nada Kusuma (Yayasan Kajian Riset dan Pengembangan RADISI, 2025)
The ASA Cendikia Program: Fostering Students’ Learning Motivation in Rendang Village is a community service initiative aimed at enhancing students’ motivation and the overall quality of education at the elementary school level in Rendang Village. The program was initiated in response to low student interest in learning and limited educational facilities, which have negatively affected students’ academic achievement. The methodology employed in this program consisted of four main stages: planning, preparation, implementation, and evaluation. The activities were carried out through collaborative involvement of university students, teachers, and local village authorities as key partners. Program activities included academic tutoring, distribution of learning materials, introduction to interactive learning methods, and motivational training for students. The results indicate a notable increase in students’ enthusiasm for learning, improved interaction between teachers and students, and heightened awareness of the importance of education. Therefore, this program is expected to serve as a sustainable model of educational empowerment that supports the enhancement of learning motivation in rural communities.